Wybrane przejawy sowietyzacji Ukraińskiej Socjalistycznej Republiki Radzieckiej na początku lat trzydziestych XX wieku w rozpoznaniu Oddziału II Sztabu Głównego Wojska Polskiego i władz politycznych II RP — część I - Landmann, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The aim of this article is to present selected facts and tendencies proving the increasing sovietization of the Ukrainian Soviet Socialist Republic in the early 1930s. The analysis is based on archival material collected in the Józef Piłsudski Institute of America and current scientific literature. A thesis was put forward that the sovietization phenomenon of the Ukrainian Soviet Socialist Republic appeared in various forms and proved harmful to the implementation of Ukrainian national slogans in the early 1930s.The presented arguments allow to conclude that at the turn of the 1920s and the 1930s sovietization replaced the earlier policy of Ukrainization in the Ukrainian Soviet Socialist Republic. The sovietization tendencies were reflected in economic reforms (especially in agriculture and industry), political and administrative transformation, or changes in the spirit of socialist society. The sovietization of the Ukrainian Soviet Socialist Republic, as an important postulate implemented by the communist authorities, was one of the forms of opposition to nationalist slogans that indicated the need for reconstruction of Ukraine independent of the Soviet Union.
Keywords: bezpieczeństwo; Oddział II SG WP; sowietyzacja; USRR